HERMÈS PHENOMENON: SOCIAL IDENTITY DEVELOPMENT THROUGH CONSUMPTIVE BEHAVIOUR AS REFLECTED IN HERMÈS TEMPTATION BY FITRIA YUSUF AND ALEXANDRA DEWI - WIGATI, PUTRI ANGGGUN (Jurnal Ilmiah Mahasiswa FIB, 2014)
People always build and develop their identities in order to gain prestigious status in their society. They often give their best and do many things inorder to be able to join a particular group. The easiest way to achieve is imitating the group’s social identity. This way is logical and reasonable because every group must have its own characteristic or symbol. Hermès as a well-knownfashion brand is an example of high class social group symbol which is generallyimitated by the middle class social group in order to enter the high class socialgroup or just to be seen equal with them. Unfortunately, when people try toachieve their main goals they are also dragged to the consumptive behavior.This research is aimed at depicting the above phenomenon as reflected inthe novel Hermès Temptation by Fitria Yusuf and Alexandra Dewi. Thus, thisresearch employs cultural study approach as the grounding theory, supported byconsumerism and social identity to analyze the relation between consumerism and social identity development. The focus of the research is on the female characters. Therefore, this research will show how the female characters in the novel Hermès Temptation developing their social identity through consumptive behavior.The result of this research shows that consumptive behavior develops thecharacter’s social identity. For high class women, Hermès is a means ofexpressing their existence. As for the middle class women, Hermès is utilized tomake their way to enter the high-class women community and develop their social identity to be seen equal to the high class women. Thus, it can be concluded that women use Hermès as the most effective media to develop their social identity. Keywords: Social Identity, Consumerism, Hermès